Development of an International Odor Identification Test for Children: The Universal Sniff Test - Schriever, Valentin A.; Agosin, Eduardo; Altundag, Aytug; Avni, Hadas; Van, Helene Cao; Cornejo, Carlos; De Los Santos, Gonzalo; Fishman, Gad; Fragola, Claudio; Guameros, Marco; Gupta, Neelima; Hudson, Robyn; et al. (Elsevier Science Inc., 2018)
Objective To assess olfactory function in children and to create and validate an odor identification test to diagnose olfactory dysfunction in children, which we called the Universal Sniff (U-Sniff) test. Study design This is a multicenter study involving 19 countries. The U-Sniff test was developed in 3 phases including 1760 children age 5-7 years. Phase 1: identification of potentially recognizable odors; phase 2: selection of odorants for the odor identification test; and phase 3: evaluation of the test and acquisition of normative data. Test-retest reliability was evaluated in a subgroup of children (n = 27), and the test was validated using children with congenital anosmia (n = 14). Results Twelve odors were familiar to children and, therefore, included in the U-Sniff test. Children scored a mean +/- SD of 9.88 +/- 1.80 points out of 12. Normative data was obtained and reported for each country. The U-Sniff test demonstrated a high test-retest reliability (r(27) = 0.83, P < .001) and enabled discrimination between normosmia and children with congenital anosmia with a sensitivity of 100% and specificity of 86%. Conclusions The U-Sniff is a valid and reliable method of testing olfaction in children and can be used internationally.
Vývoj mezinárodního čichového testu identifikace pro děti: Univerzální Sniff Test
Keywords: test cc-sit; olfactory function; clinical-assessment; normative data; turkish population; cystic-fibrosis; life-span; smell; sticks; dysfunction; Sniffin' Sticks; děti; čich; porucha čichu; vyšetření čichu